AN ANALYTICAL REVIEW OF THE RELATIONSHIP BETWEEN SCIENCE AND PHILOSOPHY & THEIR UTILITY IN CONTEMPORARY GLOBAL POLITY CONCEPTUALIZATION OF TECHNOLOGY - SIMUZIYA, NSAMA JONATHAN; JALU, ABEBE TIGIRE (Science and Innovation, 2023)
Introduction. The central argument of this study is that for science to meet the challenges of globalization and justice in the 21st century, it needs to be ethically informed, and thus philosophical reflection on and in science is cardinal. Problem Statement. The study focuses on the 21st century trends in philosophical thoughts that influence scientific motivations. To this effect, the research question that the study sought to answer is, ‘How and to what extent can philosophy be valuable/influential to scientific advancements in contemporary times?’ Purpose. This paper aims to demonstrate that despite some differences between science and philosophy in their origin and methodological conceptions, they do have reciprocal rudiments. The study gleaned this relationship with the view to assess the utility of their relationship in a technologically and fast-paced 21st Century. This study contributes to the literature by providing theoretical perspectives that critique conventional (Western) epistemic stances of scientific knowledge construction and highlights lessons to be learnt through a juxtaposed pool of ideas from all regions of the globe, not just from the West. Material and Methods. The methodology adopted for this study leans on a descriptive and thematic literature approach which builds on qualitative data gathered through academic journals, scholarly books, and online publications. The study review endeavors to focus on the 21st century trends in philosophical thoughts that influence scientific motivations. Results. The study notes that the relationship between science and philosophy has endured for many hundreds of years, and despite their differences which mainly lie in their scope, attitudes, methods, and peculiar challenges, both are keenly engaged in advancing increased human capacity for innovation, ingenuity, and critical thinking. The study concludes — from the prism of the future — that a critical global appraisal and continuous rigorous review of scientific and philosophical activities is essential today more than ever before, if the futures project is to contri bute effectively to the (re)construction of sustainable frameworks of scientific production that yield results in an equitable and environmentally sustainable manner. Conclusions. The study has brought to the fore, a stark reminder that neither science nor philosophy — operating singularly — offers genuine solutions on sustainable growth and development; hence stakeholders can make sense of complex phenomenon from both science and philosophy by critically reviewing their outcomes in a reciprocal manner that appreciates the advances, the gaps, and excesses from both sides. Most significantly, the study has pushed the envelope of comprehending science and philosophy beyond Western constructions that often tend to overlook, and in some cases purposely downgrade orthodox but otherwise valuable scientific insights from subaltern constellations of the global South.